Investigating and expanding learning across activity system boundaries in improved cook stove innovation diffusion and adoption in Malawi - Jalasi, Experencia Madalitso (Rhodes University, Faculty of Education, Department of Education, 2019)
This study investigates and expands learning within and between activity systems working with Improved Cook Stoves (hereafter ICS) in Malawi. The study focuses on how existing learning interactions among ICS actors can be expanded using expansive learning processes, mobilised through Boundary Crossing Change Laboratories (BCCL) to potentially inform more sustained uptake and utilisation of the ICS technology. The ICS, as a socio-technical innovation, seeks to respond to climate change mitigation and adaptation efforts in the country. However, sustained uptake and utilisation has been problematic. The study is located in the field of Environmental Education, with emphasis on the diffusion and adoption of socio-technical innovations in the context of ICS technology. The study addresses societal environmental health risks faced by people using traditional biomass fuels indoors on open fires, commonly referred to as Three Stone Fire (hereafter TSF) through formative intervention supported by Developmental Work Research (hereafter DWR) or Expansive Learning. The study was conducted in three climate change hotspot districts in Malawi: Balaka, Dedza and Mzimba. The case studies are in each of the three administrative regions of the country. Chapita Village case study is in Balaka district, in the Southern region; Waziloya Makwakwa Village is in Mzimba district in the Northern region; and Chilije Village in Dedza district in the Central region. In order to engage the potential for transformation in study areas, I divided the study into two phases. The first phase involved collection of ethnographic data to more deeply understand the context of the problem including existing learning approaches. This informed the second phase, which focused on expansive learning processes in the Chapita and Waziloya Makwakwa case studies. The study used a formative intervention approach, which focused on supporting the actors to manage the challenges they were facing and work out the problematic situations in their joint activity. The study employed a qualitative intensive research design because it aimed at in-depth understanding of uptake and utilisation of ICS. This was an important foundation for improving the existing situations through co-creating solutions with research participants. With this generative and action-oriented approach, the study employed a multiple embedded case study design. CHAT and Critical Realism were the two main theories that I employed as they resonated with the transformative interest of the study through focusing on learning as an emancipatory process with potential for transformation of human practices. In addition, I used the methodological theory of Expansive Learning from CHAT to guide the expansive learning processes. With the critical realist framing of the study, I employed a critical realist analytical framework, and used inductive, abductive and retroductive analyses.The major findings of the study indicate that broadly, uptake and utilisation of ICS is problematic, hence unsustained. The findings indicate that the majority of end-users in Chapita and Chilije case studies switched between TSF and ICS, or abandoned the ICS, which was not the case in Waziloya Makwakwa case study. The underlying causal mechanisms that appear to explain and influence end-users' actions in all the case studies were the search for convenience during the cooking activity. Further, findings revealed that learning interactions among activity systems were unidirectional which provides evidence for top-down approaches prevalent in cook stove dissemination. The findings also indicated that most of the learning taking place was informative, not transformative. It was also inadequate, particularly for end-users. A causal mechanism that appears to shape how actors are learning ICS technology is poverty, which results in over-reliance on donor-driven projects. Findings also reveal that contradictions in the learning, uptake and utilisation of ICS influence the profile of uptake and utilisation of ICSs. Further, the change-oriented learning processes, as carried out in the Chapita and Waziloya Makwakwa case studies, have shown their potential in expanding learning interactions among ICS actors, evoking and supporting their transformative agency and enhancing their reflexivity. These processes are crucial in development and sustaining learning and change in the uptake and utilisation of ICS innovation. The main contribution of the study is methodological. It contributes broadly to diffusion and adoption of socio-technical innovations through change-oriented expansive learning processes. The study generated an Innovative Extension and Communicative Methodology, which foregrounds interaction and learning and links the socio-technical innovation intention and socio-technical innovation uptake and utilisation that potentially informs the dissemination and implementation of ICS projects. Further, the study contributes to community education by mobilising communities to address contradictions, absences, or ills in the society via change-oriented learning processes. The societal ills facing the case study sites and the areas around them, caused by climate change and variability and deforestation exacerbate the lives of rural women who are afflicted by conditions of poverty. The study contributes to global and local efforts and initiatives to address environmental health risks faced by people using traditional biomass fuels indoors on TSF and climate change mitigation and adaptation. This study has found out that putting the agency of the end-user in the centre in socio-technical transitions through context-based problem resolution and rigorous deliberate1 mediated processes of participation and learning, which allows multivoicedness and takes power relations into account, catalyses transformative agency, reflexivity, collaboration and learning capacity of ICS actors for sustained uptake and utilisation of the ICS socio-technical innovation.
Keywords: Stoves, Wood -- Technological innovations -- Malawi; Biomass stoves -- Malawi; Economic development projects -- Environmental aspects -- Malawi; Rural development projects -- Environmental aspects -- Malawi